Penerapan Algoritma C.45 Untuk Menentukan Tingkat Kepuasan Pelanggan Kartu Telkomsel Prabayar - Sikumbang, Erma Delima; Ariani, Fattya; Handayani, Tiwi; Ramanda, Kresna; Sukmana, Sulaeman Hadi; Supriyatna, Adi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Telkomsel is an operator mobile phone company that provides services for mobile phone users. The mobile phone Operator creates a small SIM card for the customer by means of having to be inserted into each phone to get access to the service. One of the most used mobile operators and belongs to the largest category in Indonesia is Telkomsel. In This study implemented algorithm method C. 45 in deciding customer satisfaction against the use of prepaid Telkomsel cards. This type of research is to implement data mining concept by involving as many as 100 user data of prepaid Telkomsel card through the dissemination of questionnaires. There is an attribute in each variable that affects customer satisfaction including: price, promotion, product quality and service quality. Based on manual calculation results and with the help of the RapidMiner studio 9.7 software is known to be the root is a variable quality service with the highest gain value of 0.266396957 and results classification accuracy value of 0.9655 so that belongs to the classification category is very good